EVALUASI KEBIJAKAN CYBER SECURITY SEKTOR PERBANKAN BANK BTN CABANG SURABAYA - Rudiatno Rudiatno; Aldea Mita Cheryta (Jurnal Apresiasi Ekonomi, 2022)
ABSTRACTThis study discusses the evaluation of cyber security policies in the banking sector at Bank BTN Surabaya using qualitative methods and data collection techniques indepth interviews and focus group discussions. The focus of this study is policy evaluation and prevention of cybercrime in banking. The location of this study was conducted at Bank BTN Prioritas Surabaya Branch, the selection of the location of this study was due to bank BTN being one of the banks that implemented preventive measures in preventing cybercrime. The problem that will be described in this article is First, How is the impact of cyber security on Bank BTN Surabaya Branch? Second, What is the government's policy strategy on cyber security? Third, How to prevent cyber-crime at Bank BTN Surabaya Branch? The conclusion of this study is that Bank BTN Surabaya shows good preventive steps by forming a special organizational structure to deal with legality issues and the implementation of cybercrime prevention applications. Bank BTN conducts policy evaluations every two weeks as a form of evaluation of target achievement and monthly evaluations carried out by their superiors directly. Furthermore, every six months Bank BTN Surabaya brings in an external audit to be able to supervise and monitor.Keywords: Bank, Cyber Security, Evaluation